EVALUASI PROGRAM PENDIDIKAN TAMAN KANAK-KANAK BERBASIS HINDU - Sedana Suci I Gede; Suyanta I Wayan (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2022)
The purpose of this research is to evaluate the programs developed at PAUD Dharma Kumara Kerthi, Lukluk Mengwi Badung. The approach used in this research is carried out qualitatively with data collection techniques implemented by methods, interviews, documentation and observations. After the collected data is analyzed using the CIPP method, namely in the form of context components Context, Input, Process, and Product. The results showed: a) the standard of documents as juridical facilities that have been determined by the government has been fulfilled, b) the financing program is important to be improved related to the maintenance of building facilities for the safety and comfort of students, c) the infrastructure supporting Hindu-based learning is not adequate, d) learning tools both indor and autdor, namely educational props (APE) with Hindu character are still very minimal in type and number; e) supporting facilities, namely learning places outside the classroom for Hindu-based are adequate.